Support Services at a Francophone University in Quebec: Contrasting Viewpoints of Chinese International Students and University Professionals - Soares, Roberta; Magnan, Marie-Odile; Liu, Yifan; Melo, Fabiola (Journal of Contemporary Issues in Education, 2024)
This qualitative study showcases the viewpoints of Chinese international students and university professionals about the services offered at a francophone university in Montreal regarding “welcoming” and “integration.” Semi-directed interviews were conducted among 22 participants, of which 14 were students and 8 university professionals. Using the concept of care, we conducted a thematic analysis. According to the analysis, students mention the lack of effective support, while university professionals discuss the support offered and its pitfalls. In terms of recommendations, we stress the importance of tackling current structural issues rather than putting the responsibility for the quality of the experience on students’ shoulders. We also emphasize that professionals who provide services directly to students must be given proper training and resources through universities to enable them to change the current paradigm and offer services that reflect the concept of student care.